ANALYSIS OF ENERGY EFFICIENCY RATIO (EER) IN AIR CONDITIONER (AC) TYPE SPLIT - Yolanita Fani; Ilham Arnif (Universitas Sultan Ageng Tirtayasa, 2019)
Cooling system is something that is already familiar to the people of Indonesia, both in domestic and industrial use. The cooling system functions to reduce the temperature of a room so that the temperature is as desired. The development of air conditioners is increasingly modern. The use of air conditioners (AC) is growing rapidly so that the CFCs produced affect the environment which can cause the ozone layer to be damaged and cause global warming. Therefore, there is a need for research related to the level of energy use. This study discusses the Energy Efficiency Ratio test to realize a government program that is